Pengaruh Motivasi, Komunikasi dan Beban Kerja Terhadap Kepuasan Kerja Karyawan pada PT. Boga Cipta Kreasi Balikpapan - Vivianne Chelsea Kezia Canovanny; Misna Ariani; Imam Arrywibowo (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study is to determine the Influence of Motivation, Communication and Workload on Employee Job Satisfaction at PT. Boga Cipta Kreasi Balikpapan. The population in this study were all employees of PT. Boga Cipta Kreasi Balikpapan with a total of 66 respondents who would be used as samples. The type of research used was quantitative research with total sampling techniques and data collection was carried out by distributing questionnaires. The research method used Smart-PLS data processing with an analysis model using outer models, inner models, basic equations and bootstrapping testing. The results of this study indicate that the variables of motivation, communication and workload have an effect and are significant on employee job satisfaction at PT. Boga Cipta Kreasi Balikpapan.